Teacher's Expressive Speech Actions in Indonesian Language Learning in Class VII of SMP Negeri 5 Satap Palakka, Bone Regency - Andi Tenri Sua; Nurfani Putri Ramadhani; Muhammad Idris (Edumaspul: Jurnal Pendidikan, 2023)
This research is a descriptive qualitative research. Based on the problem, the purpose of the research is to know the function, strategy and mode of expressive speech acts of teachers in the process of learning Indonesian language in Class VIII SMPN 5 Satap Palakka.) The forms of expressive speech act functions of teachers in the process of learning Indonesian in Class VIII SMPN 5 Satap Palakka include, expressive speech acts of greeting, insinuating, criticising, angry, and praising; 2) The teacher's strategy in applying expressive speech acts towards students in Indonesian language learning in Class VIII SMPN 5 Satap Palakka is direct and indirect expressive speech act strategies; 3) The mode of expressive speech acts applied by teachers towards students in Indonesian language learning in Class VIII SMPN 5 Satap Palakka Bone Regency includes optative, interrogative, and imperative.